A novel approach to improving a partial foot amputees gait with a 3D printed footwear - Lee, Glendon Hsien Hwee (Nanyang Technological University, 2020)
With the rising number of diabetics not just in Singapore but in other major countries as well. There has been an increase of patients who have to undergo amputations when they injure themselves or to prevent further complications from diabetes. Diabetic patients possess a higher risk of lower extremity amputation due to improper footwear or simply due to the frequency of activities that require movement in daily life. Among the available amputations available for the lower extremities, partial foot amputation has seen a rise in the number of operations. This is due to patients and medical practitioners choosing to preserve as much of the foot as possible, and as well as due to the perceived increased confidence in carrying out the procedure of the surgeons. The amputees who have undergone partial foot amputations however, are bound to face difficulties and obstacles when walking, especially amputees that have lost their metatarsal heads. Of the types of prosthesis and orthosis available to partial foot amputees, there are two overarching categories, namely ‘Above and Below Ankle’ and ‘Below Ankle’. Amputees, who did not perceive their current disability to be too serious, were fonder of Below Ankle designs of prosthesis and orthosis. This project’s objective is to study the pros and cons of current options for partial foot amputees and to design a new orthosis to allow an improvement in gait and progression of the Centre of Pressure through improved stiffness in the forefoot; that will ultimately be suitable for a trial participant, an elderly who has received a Lisfranc amputation on her left foot. The final year project starts off with consulting the podiatry team and biomechanical lab in Singapore General Hospital after some literature review. After interviewing an elderly diabetic lady who has amputation on her left foot, a need for a better form of orthosis in a form of footwear was discovered. To design a pair of footwear that was able to function as Metatarsophalangeal joints, providing feedback to the user along the Metatarsophalangeal line, Auxetic structures were used. Photogrammetry was employed to obtain the 3D profile of the stump before using a 3D modelling software to model out the footwear around it. Subsequently, 3D printing was employed as a method to produce the said footwear. Using different Auxetic structures and observing how they responded to being flexed along the Metatarsophalangeal line, an Auxetic structure was chosen to be incorporated in the design of the footwear. Portioned off samples were 3D printed with a flexible material with varying conditions in order for a comparison of stiffness values in a compression test. The results of the test were promising. A stiffness value higher than the control was achieved for the 3D printed prototype. The Auxetic structure could influence how the stiffness values of the footwear’s forefoot region changed as it was flexed. For future work, firstly the designed footwear should go through a trial period of breaking in followed by qualitative fitting and comfort tests. Secondly, in order to affirm that the designed footwear can carry out its purpose to help alleviate gait issues associated with losing one’s metatarsal head, gait analysis using pressure plates should be carried out. This determines if the progression of the Centre of Pressure is in order.